If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -4(8 + -7x) = 6(x + -5) + 7 6x + (8 * -4 + -7x * -4) = 6(x + -5) + 7 6x + (-32 + 28x) = 6(x + -5) + 7 Reorder the terms: -32 + 6x + 28x = 6(x + -5) + 7 Combine like terms: 6x + 28x = 34x -32 + 34x = 6(x + -5) + 7 Reorder the terms: -32 + 34x = 6(-5 + x) + 7 -32 + 34x = (-5 * 6 + x * 6) + 7 -32 + 34x = (-30 + 6x) + 7 Reorder the terms: -32 + 34x = -30 + 7 + 6x Combine like terms: -30 + 7 = -23 -32 + 34x = -23 + 6x Solving -32 + 34x = -23 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -32 + 34x + -6x = -23 + 6x + -6x Combine like terms: 34x + -6x = 28x -32 + 28x = -23 + 6x + -6x Combine like terms: 6x + -6x = 0 -32 + 28x = -23 + 0 -32 + 28x = -23 Add '32' to each side of the equation. -32 + 32 + 28x = -23 + 32 Combine like terms: -32 + 32 = 0 0 + 28x = -23 + 32 28x = -23 + 32 Combine like terms: -23 + 32 = 9 28x = 9 Divide each side by '28'. x = 0.3214285714 Simplifying x = 0.3214285714
| 6c=6x | | 8c=8c | | 7x(m-3n)-4y(m-3n)= | | 11x+3-4x=6x-2 | | X/-7=-20 | | 6porn=7jam | | -3+4-6x=8x+3-18x | | 2*2*22*2*22*2*22*2*2=9g | | x/(0,8-2x)^2=2 | | -879345879453897354789x=7 | | 2x+5=7x-3x+2 | | 4(0.19x+1)-4=1.03x-3.24 | | 96(x-4)-384=96x+95 | | 0.2x=64 | | A-45=13+A | | y=12(1.05)5 | | -7v+8=6-6 | | y=10(1+0.4)5 | | 4v(v+3)(v-1)=0 | | 3a+3b=2x+2y | | 18y-7y=19+5y | | 8(3x-1)=135 | | X-45=13+x | | 15x+12x+20x=300 | | 3(u-2)=4u+2 | | (-2r/8)=(30/24) | | 31x/31=x | | 8(12x+1)=96x-6 | | 12-7x=x^2 | | y=8x+55 | | Y+5x+8=0 | | 5109*0.917=x |